Customer Perception Towards E Banking Platforms - Shreyam Chaudhary (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2023)
A term that is widely used in today's society is "E-banking," which is frequently defined as the use of electronic techniques to carry out online banking operations. Modern banking procedures have undergone a substantial transformation as a result of this. One of the key strategies for attracting and retaining customers on electronic banking systems is to offer high-quality e-banking services. The purpose of this study is to experimentally investigate a comprehensive, moderated, mediated mechanism for increasing customer loyalty to e-banking systems through EBSQ practises. EBSQ has four dimensions: dependability, online design, privacy and security, and customer service and support. Due to the electronic payment, there is an increase in customer satisfaction, improved productivity, a drop in the cost of banking operations, faster settlement in large volumes, and e-banking is greatly strengthening. This brings us to a very nicequestions that “Will the present situation of banking sector shift to a totally online mode of banking services?”